2014
DOI: 10.1007/s00415-014-7283-1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic profiles of patients with late-onset Creutzfeldt–Jakob disease differ from those of younger Creutzfeldt–Jakob patients: a historical cohort study using data from the German National Reference Center

Abstract: Abstract:Background: In contrast to other neurodegenerative diseases sporadic Creutzfeldt-Jakob disease

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 15 publications
3
13
0
1
Order By: Relevance
“…A relatively low number of patients per mutation, for example in E196K, unfortunately precludes multivariate analysis, so that the interpretation of the finding that E196K patients were the oldest patients with the shortest disease course should be made with caution. However, as it is known that the most CJD patients (not so differently from patients with other dementias in the final stage) die on infections such as pneumonia, worse immunity and worse premorbid general state of health may play a role in older patients, so that they show a shorter disease course, as already described by Karch et al [22].…”
Section: Discussionmentioning
confidence: 88%
“…A relatively low number of patients per mutation, for example in E196K, unfortunately precludes multivariate analysis, so that the interpretation of the finding that E196K patients were the oldest patients with the shortest disease course should be made with caution. However, as it is known that the most CJD patients (not so differently from patients with other dementias in the final stage) die on infections such as pneumonia, worse immunity and worse premorbid general state of health may play a role in older patients, so that they show a shorter disease course, as already described by Karch et al [22].…”
Section: Discussionmentioning
confidence: 88%
“…In China, patients with sCJD were characterized by a relatively early age of onset, acute or subacute onset, obvious dementia, myoclonus and extrapyramidal motor symptoms, visual impairment and cerebellar signs appeared comparatively early, besides mild and later pyramidal tract damage, dementia is obvious, but signs of encephalatrophy were relatively less obvious. Historical studies found that older patients than 75 years showed a faster disease progression represented by an earlier point of diagnosis and a shorter survival time, they suffered slightly more often with dementia or dysarthria in the early stage of disease [9], When expanding this analysis to the entire duration of disease, patients over 75 years old had a higher risk of the pyramidal signs' presence. The above case was comparable to typical late onset sCJD profiles, and was consistent with the Chinese sCJD disease except vision loss.…”
Section: Discussionmentioning
confidence: 93%
“…MRI profiles of patients over 75 years old were significantly less frequently accordant with established MRI criteria for sCJD than MRI profiles of the younger group. Researchers found that atypical MRI profiles that showed lesions localized in one hemisphere or cortex only were found more frequently in patients over 75 years old, whereas typical cortical and basal ganglia hyperintensities were more common in the younger group [9]. The MRI profile of our current case was not in accord with sCJD patients over 75 years old, with hyperintensity only in the bilateral cerebral cortices on initial DWI and increased basal ganglia signal in addition to cortical hyperintensity on the followup image 1 month later.…”
Section: Discussionmentioning
confidence: 99%
“…An area under the receiver operating characteristic (ROC) curve for 14‐3‐3 shows a value of only 0.67, remarkably low compared to other markers in this review, but only autopsied patients were used in that specific study. The likelihood of a negative 14‐3‐3 increases the likelihood of the autopsy being performed which may bias the patient population . In 2012, a meta‐analysis of 9 independent studies and 1849 patients found that CSF 14‐3‐3 had a combined sensitivity and specificity of 92% and 80% .…”
Section: Protein Markers Of Scjdmentioning
confidence: 99%
“…Tau, a neuronal protein important in microtubule stability, has been shown to be elevated in the CSF of patients with CJD. The sensitivities and specificities of CSF total‐tau (t‐tau) range from 75 to 98% and from 67 to 99%, respectively, with the highest area under ROC reaching 0.949 . CSF tau positivity has been evaluated as having better diagnostic value compared to 14‐3‐3 in the early stages of the disease, whereas CSF 14‐3‐3 tends to be more variable toward the end stage of CJD .…”
Section: Protein Markers Of Scjdmentioning
confidence: 99%